Negative Pressure Pulmonary Edema after Reversing Rocuronium-Induced Neuromuscular Blockade by Sugammadex - Manzo Suzuki; Toshiichiro Inagi; Takehiko Kikutani; Takuya Mishima; Hiroyasu Bito (Case Reports in Anesthesiology)
Negative pressure pulmonary edema (NPPE) is a rare complication that accompanies general anesthesia, especially after extubation. We experienced a case of negative pressure pulmonary edema after tracheal extubation following reversal of rocuronium-induced neuromuscular blockade by sugammadex. In this case, the contribution of residual muscular block on the upper airway muscle as well as large inspiratory forces created by the respiratory muscle which has a low response to muscle relaxants, is suspected as the cause.